Study of Performance of a Power Station for Operational Optimisation - Sunil M. Jaralikar; Mangalpady Aruna (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Undertaking regular performance analysis of a power station is very much necessary for its operational optimization. In this regard as a case study a 630 MVA, 400/220 kV power station was identified and analysed to study its performance. The study shows that the installed station (transformer) capacity is very large compared to the load it had to supply, and also it is under loaded and underutilized for the major period of its operation. Due to this the operational efficiency of the station was reduced and also the incoming voltage level was higher than the voltage for which the station was designed. During off peak loading condition, one of the 400 kV incoming lines was being tripped, thus risking the supply reliability. This case study emphasizes and suggests few ways for improving the performance and loading pattern of the power station by optimization of its operational parameters. Keywords: Bus reactor; Energy audit; Energy efficiency; Performance analysis; Station capacity.DOI:http://dx.doi.org/10.11591/ijece.v2i1.118